2022
DOI: 10.1093/mnras/stac2579
|View full text |Cite
|
Sign up to set email alerts
|

AstroSat view of ‘Clocked’ burster GS 1826-238: broad-band spectral nature of persistent and burst emission during soft state

Abstract: In this paper, we have carried out a detailed study of the ‘Clocked’ burster GS 1826 − 238 using ∼ 90 ks broad-band (0.7 - 60.0 keV) data obtained with AstroSat observatory. The source was observed during a soft spectral state and traced a ‘banana’ type track in the colour-colour diagram (CCD). We find that a combination of thermal component (multi-colour disc/bbodyrad) and Comptonized component is statistically good description for all the sections of the track in the CCD. The corona becomes optically thick (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Finally, we attempted a combination of MCD and nthComp (hereafter Model 3) components to describe the X-ray spectra of this source. Both models have been widely used to fit the spectra of the NS-LMXBs (Di Salvo et al 2002;Di Salvo et al 2001;Barret 2001;Agrawal, Nandi, and Katoch 2023;Agrawal and Sreekumar 2003). We also need an additional smeared edge component (at ∼ 7 -8 keV) to improve the fit.…”
Section: Analysis Of Spectroscopic Datamentioning
confidence: 99%
“…Finally, we attempted a combination of MCD and nthComp (hereafter Model 3) components to describe the X-ray spectra of this source. Both models have been widely used to fit the spectra of the NS-LMXBs (Di Salvo et al 2002;Di Salvo et al 2001;Barret 2001;Agrawal, Nandi, and Katoch 2023;Agrawal and Sreekumar 2003). We also need an additional smeared edge component (at ∼ 7 -8 keV) to improve the fit.…”
Section: Analysis Of Spectroscopic Datamentioning
confidence: 99%
“…Variations in the hard flux lasted until roughly MJD 57100 (2015 March), when the hard flux completely disappeared, while the soft flux showed significant variability over a multiyear period (Figure 2, bottom panel). The ASTROSAT observations show evidence for a classical banana soft state for the source similar to the 2014 soft episode, with the emission dominated by an optically thick corona with a low electron temperature (Agrawal et al 2022).…”
Section: Gs 1826-238 Long-term Behaviormentioning
confidence: 80%
“…Other than short snapshots from NICER, one focused observation with NuSTAR, and a pair of observations using ASTROSAT (Agrawal et al 2022), until 2022 the source has not been intentionally observed since it started its transition. Fortunately, GS 1826-238 is nearby several sources with recurring outbursts (e.g., V4641 Sgr).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray spectra of the NS-LMXBs are complex and require multiple components to describe them. A combination of multi-temperature disc blackbody and Comptonized emission (Di Salvo et al 2000aAgrawal & Sreekumar 2003;Tarana et al 2008;Agrawal & Misra 2009;Agrawal et al 2023) has been widely used to describe the X-ray spectra of the atoll and Zsources. Here, the softer component from the disc is directly observed, and the Comptonized emission may come from the boundary layer (BL) or spreading layer (SL) near the surface of the neutron star ('eastern model').…”
Section: Introductionmentioning
confidence: 99%